On the role and purpose of the human being in the Zhuangzi - 邱浩崴 Koo, Hao Wei (Nanyang Technological University, 2024)
This thesis is devoted to the exposition of the Zhuangzi’s vision of the purpose and role of the human being, which is intricately connected to the Zhuangzi’s central concept, tian (天). The thesis puts forth the proposition that because the Zhuangzi sees the human being within the backdrop of a natural world arising from tian, its understanding is that the human being shares its place equally amongst the myriad things and thus the purpose of the human being is to partake in the spontaneous generation of things as themselves, all the while refraining from interfering with other things’ being themselves. The thesis consists of two chapters. In the first chapter, I introduce the central concept of tian in the Zhuangzi alongside some background information about the Chinese character tian and its usages in other philosophical texts in the Pre-Qin period. In the second chapter, basing on the understanding of tian in the first chapter, I highlight the potential conflict that the Zhuangzi pointed out between tian and the human being and looked at the impact of human preferentiality which the Zhuangzi sees as problematic. Combining the understanding that the Zhuangzi sees the human being in the backdrop of the natural world as arising from tian, I arrive at the interpretation that the Zhuangzi envisions the human being who shares an equal position among the myriad things, partaking in the spontaneous generation of things themselves and refraining from interfering with the course of other things’ being themselves. Thereafter, I attempt to address its inconsistency with the Zhuangzi’s passages on the hasty distinction of tian and the human.